Personal Hygiene Traders in the Central Market during the 2021 Covid-19 Pandemic - Abdullah, Hajrah; Susilawaty, Andi; Syarifuddin, Nurdiyanah (HIGIENE: Jurnal Kesehatan Lingkungan, 2021)
Personal hygiene is very important for traders to pay attention to in order to minimize contact and the possibility of transmission of the Covid-19 virus. This study aims to determine the personal hygiene of traders during the COVID-19 pandemic in 2021. The type of research used is a quantitative research with a descriptive approach. The population in this study were all traders in the Bulukumba Central Market with a total sample of 88 traders. The sampling technique used is random sampling technique. The results of this study indicate that the knowledge of traders about personal hygiene during the Covid-19 pandemic is in the good category, namely 97.7%, the attitude of all traders in the good category is 100%, the actions of traders in the good category are 85.2%. The results of this study also show that personal hygienewith good category as many as 52 respondents (59.1%). It is expected that traders will still have to comply with every government regulation in preventing Covid-19 by using masks, keeping a distance or social/physical distancing, applying cough etiquette, always washing hands using soap and running water, diligently cleaning or spraying disinfectants on frequently touched objects. , consuming nutritious food, and also the importance of accessing reliable sources of information about personal hygiene during the Covid-19 pandemic that is good and correct.